2008
DOI: 10.2167/joe137.0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Interpretation Evaluation in Natural Areas

Abstract: Environmental interpretation is widely assumed to influence visitor behaviour and reduce impacts on a natural site. Assumptions of cause and effect are difficult to attribute and relatively few studies evaluate the effects of interpretation on visitor behaviours. We reviewed a sample of the interpretation evaluation literature available through online databases. We looked at the internal validity of evaluative studies and compared different interpretive approaches in terms of outcomes. Findings indicate an eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 42 publications
1
87
1
5
Order By: Relevance
“…Preliminary research suggests that interpretive programmes can increase feelings of nature connectedness, particularly if they complement knowledge-based learning with emotional connections to nature or to place. However, research on the influence of interpretive programming on behaviours in natural areas is limited and lacks robustness (Munro et al, 2008;Weiler et al, 2013).…”
Section: Parks Vol 212 November 2015mentioning
confidence: 99%
“…Preliminary research suggests that interpretive programmes can increase feelings of nature connectedness, particularly if they complement knowledge-based learning with emotional connections to nature or to place. However, research on the influence of interpretive programming on behaviours in natural areas is limited and lacks robustness (Munro et al, 2008;Weiler et al, 2013).…”
Section: Parks Vol 212 November 2015mentioning
confidence: 99%
“…A number of studies have succeeded in identifying and measuring specific cognitive (knowing), affective (feeling) and behavioural (doing) outcomes of interpretation (see for example the reviews by Weiler, 2006 andMunro et al, 2008), including the impacts of interpretation in zoos, aquariums and non-captive wildlife settings (e.g. Adelman et al, 2000;White and Jacobson, 1994;Orams, 1994;Dierking et al, 2002;Rabb, 2004;Randler et al, 2007;Swanagan, 2000).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similarly, a synergic eff ect between the interpretive trail and whether a respondent was interviewed outside INT, before INT or after INT was not proven (Table 5). Th erefore, these results can be better generalised than those of studies of individual localities (see, for example, Jacobs and Harms, 2014;Munro, Morrison-Saunders and Hughes, 2008). Th ere is a signifi cant diff erence in scores by outside INT, before INT or after INT group (Figure 3).…”
Section: Environmental Knowledgementioning
confidence: 81%
“…Previous studies have shown that environmental education can encourage pro-environmental behaviour (Jacobs and Harms, 2014), and trails' importance for environmental knowledge is indisputable (Angelini et al, 2011), although some information communicated on trails can be non-objective (Braithwaite and Leiper, 2010), and visitors' future behaviour does not necessarily display more environmental friendliness in the long term (Hughes, 2013). A detailed overview of these papers can be found in Munro, Morrison-Saunders and Hughes (2008). Interpretive trails are one of the most widely used tools in environmental education in large protected areas in Central and Eastern European countries (Cetkovsky et al, 2007;Foret and Klusacek, 2011;Svec et al, 2012;Frantal and Urbankova, 2014;Kroupova et al, 2014), and there is a notion that all visitors to protected areas visit interpretive trails, much like other backbone sites, such as chateaux, castles and castle ruins (Zelenka et al, 2013).…”
Section: Environmental Education In Tourismmentioning
confidence: 99%